Association of high serum soluble interleukin 2 receptor levels with risk of adverse events in patients with cardiac sarcoidosis. (14th October 2021) - Kobayashi, Y; Nagai, T; Hirata, K; Tsuneta, S; Kato, Y; Komoriyama, H; Kamiya, K; Konishi, T; Sato, T; Omote, K; Ohira, H; Kudoh, K; et al.
Abstract: Background: Sarcoidosis is a systemic granulomatous disease that affects multiple organs. Among these, the presence of cardiac involvement is recognised as a determinant of worse clinical outcomes. Soluble interleukin 2 receptor (sIL-2R) is a potentially useful biomarker in the diagnosis and evaluation of disease severity in patients with sarcoidosis. However, it remains to be seen whether sIL-2R is associated with the severity and activity of disease in patients with cardiac sarcoidosis (CS). Purpose: The aims of this study were to investigate whether sIL-2R was associated with clinical outcomes and to clarify the relationship between sIL-2R levels and disease activity evaluated by 18F-fluorideoxyglucose in positron emission tomography/computed tomography (18F-FDG PET/CT) in patients with CS. Methods: We examined 101 consecutive patients with CS who were admitted to our University HospitalbetweenMay 2003 and February 2020. Patients who had no data of serum sIL-2R levels before initiation of immunosuppressive therapy (n=18) were excluded. Ultimately, 83 patients were examined in this study. The primary outcome was a composite of advanced atrioventricular block (AVB), ventricular tachycardia or ventricular fibrillation (VT/VF), heart failure hospitalisation, and all-cause death. Inflammatory activity in the myocardium and lymph nodes were assessed by18F-FDG PET/CT. We used a published program to analyse the cardiac metabolic activity (CMA), and total lymph node glycolysis (TLyG), which are quantitative measures of FDG volume-intensity. Results: During a median follow-up period of 2.96 (interquartile range 2.24–4.27) years, the primary outcome occurred in 24 patients (29%), including 1 advanced AVB, 13 VT/VF, 5 hospitalisations for heart failure, and 5 all-cause deaths. Kaplan-Meier analyses showed that the primary outcome occurred more frequently in patients with higher sIL-2R levels (>538 U/mL, the median) than in those with lower sIL-2R levels (Figure). A multivariable Cox regression analysis revealed that a higher sIL-2R level was independently associated with an increased subsequent risk of adverse events (hazard ratio 3.71, 95% confidence interval 1.63–8.44, p=0.002), even after adjustments for age, plasma B-type natriuretic peptide, estimated glomerular filtration rate, left ventricular ejection fraction, and late gadolinium enhancement, which are known to be strong determinants of worse clinical outcomes in patients with CS (Table). Furthermore, sIL-2R levels were significantly correlated with TLyG, the inflammatory activity in lymph nodes (r=0.346, p=0.003) but not with CMA, the inflammatory activity in myocardium (r=0.131, p=0.27). Conclusions: Increased sIL-2R is associated with worse long-term clinical outcomes accompanied by increased systemic inflammatory activity in CS patients. These findings suggest the importance of assessing sIL-2R as a surrogate marker for further risk stratification in these patients. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Japan Society for the Promotion of Science